Non-invasive Characterization of Human AV-Nodal Conduction Delay and Refractory Period During Atrial Fibrillation - Karlsson, Mattias; Sandberg, Frida; Ulimoen, Sara R.; Wallman, Mikael (Frontiers in Physiology, 2021)
During atrial fibrillation (AF), the heart relies heavily on the atrio-ventricular (AV) node to regulate the heart rate. Thus, characterization of AV-nodal properties may provide valuable information for patient monitoring and prediction of rate control drug effects. In this work we present a network model consisting of the AV node, the His bundle, and the Purkinje fibers, together with an associated workflow, for robust estimation of the model parameters from ECG. The model consists of two pathways, referred to as the slow and the fast pathway, interconnected at one end. Both pathways are composed of interacting nodes, with separate refractory periods and conduction delays determined by the stimulation history of each node. Together with this model, a fitness function based on the Poincare plot accounting for dynamics in RR interval series ´ and a problem specific genetic algorithm, are also presented. The robustness of the parameter estimates is evaluated using simulated data, based on clinical measurements from five AF patients. Results show that the proposed model and workflow could estimate the slow pathway parameters for the refractory period, R_min^SP and ∆R^SP, with an error (mean ± std) of 10.3±22 ms and -12.6±26 ms respectively, and the parameters for the conduction delay, D_min,tot^SP and ∆D_tot^SP, with an error of 7±35 ms and 4±36 ms. Corresponding results for the fast pathway were 31.7±65 ms, -0.3±77 ms, and 17±29 ms, 43±109 ms. These results suggest that both conduction delay and refractory period can be robustly estimated from non-invasive data with the proposed methodology. Furthermore, as an application example, the methodology was used to analyze ECG data from one patient at baseline and during treatment with Diltiazem, illustrating its potential to assess the effect of rate control drugs.